Microbial Exudates as Biostimulants: Role in Plant Growth Promotion and Stress Mitigation - Mariya Ansari; B. Megala Devi; Ankita Sarkar; Anirudha Chattopadhyay; Lovkush Satnami; Pooraniammal Balu; Manoj Choudhary; Muhammad Adnan Shahid; A. Abdul Kader Jailani (MDPI AG, 2023)
Microbes hold immense potential, based on the fact that they are widely acknowledged for their role in mitigating the detrimental impacts of chemical fertilizers and pesticides, which were extensively employed during the Green Revolution era. The consequence of this extensive use has been the degradation of agricultural land, soil health and fertility deterioration, and a decline in crop quality. Despite the existence of environmentally friendly and sustainable alternatives, microbial bioinoculants encounter numerous challenges in real-world agricultural settings. These challenges include harsh environmental conditions like unfavorable soil pH, temperature extremes, and nutrient imbalances, as well as stiff competition with native microbial species and host plant specificity. Moreover, obstacles spanning from large-scale production to commercialization persist. Therefore, substantial efforts are underway to identify superior solutions that can foster a sustainable and eco-conscious agricultural system. In this context, attention has shifted towards the utilization of cell-free microbial exudates as opposed to traditional microbial inoculants. Microbial exudates refer to the diverse array of cellular metabolites secreted by microbial cells. These metabolites enclose a wide range of chemical compounds, including sugars, organic acids, amino acids, peptides, siderophores, volatiles, and more. The composition and function of these compounds in exudates can vary considerably, depending on the specific microbial strains and prevailing environmental conditions. Remarkably, they possess the capability to modulate and influence various plant physiological processes, thereby inducing tolerance to both biotic and abiotic stresses. Furthermore, these exudates facilitate plant growth and aid in the remediation of environmental pollutants such as chemicals and heavy metals in agroecosystems. Much like live microbes, when applied, these exudates actively participate in the phyllosphere and rhizosphere, engaging in continuous interactions with plants and plant-associated microbes. Consequently, they play a pivotal role in reshaping the microbiome. The biostimulant properties exhibited by these exudates position them as promising biological components for fostering cleaner and more sustainable agricultural systems.